Influence of SiAlON addition on the microstructure development of hot-pressed ZrB2–SiC composites. Issue 11 (1st August 2020) - Nguyen, Thang Phan; Ghassemi Kakroudi, Mahdi; Shahedi Asl, Mehdi; Ahmadi, Zohre; Sabahi Namini, Abbas; Delbari, Seyed Ali; Van Le, Quyet; Shokouhimehr, Mohammadreza
Abstract: The impact of SiAlON on densification behavior and microstructure of the ZrB2 -SiC composite was investigated. ZrB2, SiC, and SiAlON were used as the initial materials to produce ZrB2 -SiC composite by hot pressing at 1900 °C. A fully dense composite was obtained having ~99.9% relative density. High-resolution X-ray diffraction (HRXRD) assessment verified the in-situ formation of ZrC, and the presence of residual carbon, SiAlON, and ZrB2 and SiC phases in the as-sintered ceramic. Furthermore, the thermodynamic calculations confirmed the results attained by HRXRD. In addition, scanning electron microscopy (SEM) and transmission electron microscopy (TEM) were utilized for the microstructural investigation. SEM fractographs indicated the impact of SiAlON on the hindering of grain growth and the formation of flaky phases (graphitized carbon or solidified liquid phase) at the grain boundaries. TEM studies revealed the presence of a transparent glassy phase at the particle interfaces. A significant impact of liquid phase sintering was also affirmed in the clean interfaces.